This may not be very pretty.
(2x + 5) * (2x + 5) expanded is (use foil)
F = 4x^2
O = 2x * 5 = 10x
I = 2x + 5 = 10x
L = 25
Total = 4x^2 + 20x + 25
(x + 3)(x + 3) = x^2 + 6x + 9 by the same method
(2x + 7)(2x + 7) = 4x^2 + 28x + 49 Same method.
4x^2 + 20x + 25 + x^2 + 6x + 9 = 4x^2 + 28x + 49
5x^2 + 26x + 34 = 4x^2 + 28x + 49 Collect everything on the left.
x^2 - 2x - 15 = 0
(x - 5)(x + 3) = 0
x + 3 will have no meaning.
x - 5 = 0
x = 5
2x + 5 = 2*5 + 5 = 15
x + 3 = 5 + 3 = 8
2x+ 7 = 2*5 +7 = 17
Check
15^2 + 8^2 = 17^2
225 + 64 = ? 289
289 = 289
a = 15 <<<<< answer
b = 8 <<<<< answer
c = 17 <<<<< answer
Answer:
8+18+20x16 ,
Step-by-step explanation: yeah .
Answer:
x
=
11.12130872
Step-by-step explanation:
if this isnt right then let me know
Answer: - 6xy/23xy
Step-by-step explanation:
They're both simplified by 11.